Analysis of the Impact of Fiscal Decentralization on Regional Fiscal Imbalances: A Cross-Region Case Study in Java - Ginanjar, Rah Adi Fahmi; Sutjipto, Hady; Sugiyarto, Sugiyarto; Rahmat, Basuki; Hadi, Samsul; Sardjasasmita, Agi (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality —  This study contributes to the discourse on fiscal decentralization by examining the impact of Law Number 1 of 2022 on Intergovernmental Financial Relations (UU HKPD) and the Transfer to Local Government (TKD) mechanism in Indonesia. Unlike previous studies, this research provides a comparative analysis of vertical fiscal imbalances (VFI) and horizontal fiscal imbalances (HFI) before and after the enactment of the HKPD Law, with a specific focus on local governments in Java.  Research Objectives —  The primary objective of this study is to analyze the extent and trends of VFI and HFI      resulting from fiscal policy, particularly through the TKD mechanism, both before and after the implementation of the HKPD Law. It further assesses the effectiveness of Revenue Sharing Funds (DBH) and the General Allocation Fund (DAU) in mitigating fiscal disparities at the regional level.  Research Methods —  This study employs quantitative analysis, utilizing the Williamson Index, Theil Index, and Standard Deviation to measure fiscal imbalances. The research dataset consists of local government financial reports covering the period of 2018–2023.  Empirical Results —  The findings indicate that VFI between the central and regional governments declined following the implementation of the HKPD Law, as evidenced by improved DBH allocations. Meanwhile, HFI      initially increased but exhibited a downward trend in the post-HKPD period, with DAU playing a crucial role in reducing disparities among local governments. However, fiscal imbalances persist due to Indonesia’s expenditure assignment principle, which grants local governments autonomy over expenditures while limiting their ability to generate revenue effectively.  Implications —  The study confirms that the TKD policy under the HKPD  Law has effectively reduced fiscal imbalances but remains insufficient to fully eliminate them due to structural constraints in local revenue generation. Policymakers should focus on strengthening local taxing power, optimizing regional revenue potential, and improving fiscal administration to enhance fiscal autonomy. Future research should consider longer timeframes and broader geographical coverage to evaluate comprehensively fiscal decentralization policies.